Role of Credit Information Sharing and the Funding Cost of Banks: Evidence from the Top Ten “AA Rating” Commercial Banks of Pakistan - Ramzan Ali; Sami Ullah Butt; Zahir Zahid Butt; Shahid Manzoor Shah; Fiaz Ahmad Sulehri (SEISENSE Journal of Management, 2019)
Purpose - The objective of the study is to investigate the relationship between the credit information sharing and the funding cost of banks of the top ten “AA rating” commercial banks of Pakistan as the Commercial banks also play a significant role in the economy of every country. Design/Methodology - In this study, panel data were analyzed from 2011 to 2017. We selected the top ten “AA rating” banks from Pakistan credit rating agency (PACRA) website, and data related to another related variables are obtained from financial statements of the respective banks. Generalized Method of Moments (GMM) statistical technique was employed to measure the relationship among related variables. Findings - The result of the study shows that there is a negative and significant relationship between credit information sharing, operation efficiency, and funding cost. On the other side, profitability has a positive and significant relationship with the funding cost of the bank. Practical Implications - To manage the funding cost policymakers must focus two key findings which are credit information sharing and operational efficiency of bank and set up a credit information sharing institutions which help to reduce information irregularity and ultimately manage the funding cost of the banks.